Consumer Protection in Concluding E-Contracts In light of Palestinian Law - Tariq Kameel, Ramzi Madi, (Opción, 1970)
This research has tried to address the most important problems related to the impact of the IT revolution on the consumer who concludes contracts through the Internet. This research addressed the definition of the consumer in the contract on the Internet and the statement of privacy and differences from the ordinary consumer and the reasons to justify its protection; it also deals with the measures developed by the Palestinian legislator for consumer protection via analytical descriptive approach. As a result, this article shows the importance of the need to provide the necessary protection for the consumer who contracts through modern means of communication.